A Human Stem Cell-Derived Brain-Liver Chip for Assessing Blood-Brain-Barrier Permeation of Pharmaceutical Drugs - Leopold Koenig; Anja Patricia Ramme; Daniel Faust; Manuela Mayer; Tobias Flötke; Anna Gerhartl; Andreas Brachner; Winfried Neuhaus; Antje Appelt-Menzel; Marco Metzger; Uwe Marx; Eva-Maria Dehne (Cells, 2022)
Significant advancements in the field of preclinical in vitro blood-brain barrier (BBB) models have been achieved in recent years, by developing monolayer-based culture systems towards complex multi-cellular assays. The coupling of those models with other relevant organoid systems to integrate the investigation of blood-brain barrier permeation in the larger picture of drug distribution and metabolization is still missing. Here, we report for the first time the combination of a human induced pluripotent stem cell (hiPSC)-derived blood-brain barrier model with a cortical brain and a liver spheroid model from the same donor in a closed microfluidic system (MPS). The two model compounds atenolol and propranolol were used to measure permeation at the blood–brain barrier and to assess metabolization. Both substances showed an in vivo-like permeation behavior and were metabolized in vitro. Therefore, the novel multi-organ system enabled not only the measurement of parent compound concentrations but also of metabolite distribution at the blood-brain barrier.